KINERJA BAGIAN UMUM DAN TATA USAHA SEKRETARIAT PEMERINTAH DAERAH KABUPATEN DONGGALA - Sidha, Widya Kastrena LRTP. Dharma (Katalogis, 2019)
This study uses qualitative descriptive research. In these types of research are general, accurate, accurate and accurate, the facts, the properties and relationships of the phenomena investigated from the general to the specific. In this study, the procedure for determining informants was done by purposive sampling. In order to obtain valid and accurate data and information, in-depth interviews are conducted, with informants being used by resource persons. From the research it can be concluded that the results showed that. From these indicators, these indicators are productivity, service quality, and accountability that have not been running well or are still bad. While the factors of responsiveness and responsibility have gone hand in hand with this responsiveness factor in providing capabilities and enabling priority programs to be carried out. As for the responsibility has been going well the program because it has been running based on the existing administrative principles, according to what is expected. Therefore, the results of the study revealed that the performance of the employees of the Regional Government of Donggala in carrying out its functions did not proceed adequately because there were still more indicators in it than the secretariat of the Donggala District Government.